The Role of Facilitators in Improving Business Profitability of MSMEs Customers of BTPN Syariah Sapuran Wonosobo - Fironika, Firda Cahaya; Nisa, Fauzatul Laily; Oktafia, Renny (Unram Journal of Community Service, 2025)
The MSMEs mentoring program that took place in the Sapuran area, Wonosobo, aims to provide support to BTPN Syariah customers, especially women from productive communities. This activity focuses on empowering and increasing the capacity and skills of customers so that their businesses can develop sustainably. In addition, this program also aims to expand market access, both offline and online. The implementation of this service is carried out using training methods, written interviews, SWOT Analysis (Strength, Weakness, Opportunity, Threat), and Filling out mini surveys. Training for mentoring includes Introduction activities, Material Delivery, Material Review, and (Practice and Closing). This is done to see the condition of BTPN Syariah customers in running their businesses. The results show that this routine mentoring process has proven to be successful in helping many BTPN Syariah customers. This is evidenced by the results of a mini survey that has been conducted by the facilitator. Although previously there were customers who had difficulty in managing their businesses optimally, the presence of facilitators in this mentoring has brought significant changes. Now, their businesses are showing positive developments. By understanding and implementing the material that has been delivered during the mentoring process, the client can gain new advantages in running their business in the future. This program contributes to a significant increase in sales revenue and the development of the client's entrepreneurial skills. Thus, this mentoring program can increase capacity and empower the client's business to achieve great success in the future.